Comparative Analysis of Ranking Methods of WASPAS+ROC with Preference Selection Index (PSI) in Determining the Performance of Young Lecturers - Fince Tinus Waruwu; M Mesran (IJISTECH (International Journal of Information System and Technology), 2021)
Young Lecturers are lecturers who have a relatively new tenure compared to lecturers who have served more than 10 (ten years) at a university. Assessment of the performance of young lecturers at universities is very necessary, it aims to get an assessment of the performance achievements of the tri dharma of higher education that have been passed in several years. In order for the assessment of performance achievements to be more effective, a method is needed in generating decisions. In this study, an analysis of the combination of the Weighted Aggregated Sum Product Assessment (WASPAS) and Rank Order Centroid (ROC) methods was carried out with the Preference Selection Index (PSI) method. The WASPAS method is a ranking method that requires weights. For this reason, the ROC method is used to generate weight values. While the PSI method is a PSI method that is used to rank without the need for a weight value for each attribute. The results showed that alternative A1 is the best alternative with the highest performance with a value of 0.323 (WASPAS+ROC method) and a value of 2.016 (PSI method).